A brief history of antidepressant drug development: from tricyclics to beyond ketamine. Issue 6 (1st February 2018) - Pereira, Vitor Silva; Hiroaki-Sato, Vinícius Antonio
Abstract : Objective: Although monoaminergic-targeted drugs have prompted great advances in the development of treatments for depression, the need for new options persists, since these drugs still have a delayed clinical effect and most patients do not respond properly to them. Recently, the observation of the antidepressant effects of ketamine brought on a new wave of studies regarding the comprehension of the neurobiology of depression and the development of new and more effective antidepressant drugs. Methods: Thus, in this paper, we present a historical review of the development of monoaminergic antidepressant drugs and the role of ketamine as the introductory agent of a new era in the research of the neurobiology of depression. Results: Firstly, we review how the pharmacological treatment for major depression started, and we point out the main drugs discovered, the researchers involved, and how the studies developed have contributed to the understanding of the neurobiology of depression. Secondly, the major problems regarding the clinical efficacy and acceptance of these drugs are discussed, and the introduction of the glutamatergic system as a target for antidepressant drugs is presented. Finally, we review how ketamine revealed itself as an exciting option towards obtaining pharmacological agents to treat depression, through the understanding of biological markers. Discussion: Ketamine contributed to confirm that different targets of the glutamatergic system and neurotrophic pathways are strictly related to the neurobiology of depression. There are several antidepressant drugs based on ketamine's mechanism of action already in the pipeline, and glutamatergic-targeted antidepressants may be on the market in the near future.